1999
DOI: 10.1038/sj.bdj.4800256
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride release, weight loss and erosive wear of modern aesthetic restoratives

Abstract: 265 RESEARCHrestorative dentistry limited the scope of conventional GICs in clinical application. More recently-introduced resin ionomers have less water sensitivity, and improved aesthetic and mechanical properties. 11 However, there are great differences between various materials in the levels of fluoride released, 12 and there is also less fluoride released when artificial 13 and human saliva 14 are used, rather than deionised water. Some materials claimed by their manufacturers to release fluoride hardly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 25 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…It is known that during consumption, food or drink contact only shortly with the tooth surfaces before they are washed away by saliva. However, in previous studies, substrates usually contacted acidic foodstuffs for a prolonged period of time or did not account for the role of saliva (11–17). The present study was designed to overlap the above‐mentioned limitation of in vitr o studies, by employing a dynamic erosive pH‐cycling model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that during consumption, food or drink contact only shortly with the tooth surfaces before they are washed away by saliva. However, in previous studies, substrates usually contacted acidic foodstuffs for a prolonged period of time or did not account for the role of saliva (11–17). The present study was designed to overlap the above‐mentioned limitation of in vitr o studies, by employing a dynamic erosive pH‐cycling model.…”
Section: Discussionmentioning
confidence: 99%
“…Various assessment techniques have been applied to evaluate the degradation of dental materials and the loss of dental hard tissue by erosive challenges, such as microhardness (11, 13, 14, 20, 21), surface roughness (21, 22), weight changes (15), compressive, biaxial flexure and shear punch strength (12, 16) and wear (15, 17). Initially, the aim of this study was to assess the effect of an erosive pH cycling on different restorative materials and also on the enamel adjacent to these materials.…”
Section: Discussionmentioning
confidence: 99%
“…According to Turssi, et al 25 , based on the erratic behavior pattern shown by Photac-Fil as a result of NNaF gel and APF gel treatment, degradation depends not only on the pH of the gel, but probably also on the gel’s ability to form a complex structure with the metal ions of the restorative material. Yip, et al 30 suggested that Ra values of the Photac-Fill were comparable to the conventional GICs, and according to these investigators it is possible that stresses built up in the glass particle-resin matrix interfaces. Hadley, et al 13 and Billington, et al 1 demonstrated that immersion of Photac-Fil in 0.02% NNaF solution for 24 h results in surface roughening of about 310-370%.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that topical fluoride application to compomers could increase the surface roughness of this materials 3,7,30 -32. The clinical significance of the increased surface of the materials covers the increased plaque adhesion and its harmful effects on the tooth and periodontium, to surface discoloration and fatigue failure 2-3,12,19,22,29 .…”
Section: Introductionmentioning
confidence: 93%
“…Glass ionomer cement (GIC) is considered to be a fluoride reservoir which maintains a steady flow of fluoride ions into the surrounding tooth structure, thus enhancing the resistance to secondary caries. [ 1 2 ] However, inadequacy of conventional GIC to be used in stress-bearing area has led to the development of newer fluoride-releasing materials with better physical properties.…”
Section: Introductionmentioning
confidence: 99%